Policy transfer in Malaysia: a case study of National Biotechnology Policy / Ravi Mahalingam - Mahalingam, Ravi (2014)
In recent years, policy literature has increasingly paid attention to the studies of policy transfer. Today, policy makers from all over the world draw lessons both from their own country’s experience and the practice of other nations in seeking best practice for the betterment of their own. In Malaysia, policy transfer is more evidence in the economy and technology policy, for instance, in the development of National Biotechnology Policy. Malaysia has identified biotechnology as one of its new engine of economic growth and thus a comprehensive policy on the subject matter is important to ensure the success of the industry. This paper attempts to address the process of policy transfer in Malaysia, especially in the development of National Biotechnology Policy. Using the voluntary policy transfer network model as a conceptual framework, it attempts to investigate why, how, and when policy transfer occurs, paying particular attention to the role of policy actors in the process. The major findings of this paper can be classified into two. Firstly, policymakers in the developing countries like Malaysia often assume central roles in initiating, shaping and pursuing public policies. Secondly, a well mobilized policy consultants and policy network is important in ensuring a successful public policy development.